TANGGAPAN MASYARAKAT DESA TERPENCIL TERHADAP WAJIB BELAJAR 9 TAHUN (Studi Kasus Masyarakat Munti Gunung Kabupaten Karangasem) - Suciptawati, Ni Luh Putu; Asih, Made; Sri Artini, Ni Nyoman (PIRAMIDA, 2012)
The 9 years compulsory education program purposes to give minimum education to the Indonesian citizen for developing their potency in order to live independently in their community or to continue their education to the higher education. This research aimed to know  response of isolated Village Community towards 9 years compulsory education program and also the variables that influencing those responses. This research located at Munti Gunung Village The variables that identifies influencing the responses of Munti Gunung Village Community towards 9 years compulsory education program is analyzed through multinomial logistic regression method. From 221 samples, 66,52  per c en t families support the program, 5,43 per c en t families are apathetic, and 28,05 per c e t families do not support the program of 9 years compulsory education program. The result that is analyzed by multinomial logistic regression method produces the best models: The apathetic statement that is compared with support ed statement model. g 1 ( x )= -28,27236 + 22,45813 x 1 – 0,00000896 x 7 + 0,2349989 x 2 – 1,90424 x 3 The unsupported statement that is compared with supporting statement model. g 2 ( x ) = -9.427904 + 3.773763x 1 - 0.00000901x 7 + 0.2554591x 2 - 1.011138x 3 Based on the best models that are formed, the independent variables that significantly influencing the responses of the Munti Gunung Village Community towards 9 years compulsory education program are children’s sex (x 1 ) and the age of the head of family (x 2 ), both of those variables are influencing positively, otherwise the head of family’s education (x 3 ) and family’s income (x 7 ) influencing negatively. The determination coefficient value that is formed based on the best model is 60, 57  per c en t.
Keywords: 9 years compulsory education program; the responses of community; multinomial logistic regression